6-Gingerol, a Major Ingredient of Ginger Attenuates Diethylnitrosamine-Induced Liver Injury in Rats through the Modulation of Oxidative Stress and Anti-Inflammatory Activity. (19th January 2021) - Alsahli, Mohammed A.; Almatroodi, Saleh A.; Almatroudi, Ahmad; Khan, Amjad Ali; Anwar, Shehwaz; Almutary, Abdulmajeed G.; Alrumaihi, Faris; Rahmani, Arshad Husain
Abstract : Diethylnitrosamine (DEN) is a well-known hepatocarcinogen, and its oral administration causes severe liver damage including cancer. DEN induces the pathogenesis of the liver through reactive oxygen species mediated inflammation and modulation of various biological activities. 6-Gingerol, a major component of ginger, is reported to prevent liver diseases by reducing the oxidative stress and proinflammatory mediators. The present study investigated the hepatoprotective effects of 6-gingerol through the measurement of oxidative stress, anti-inflammatory markers, liver function enzyme parameter, and histopathological analysis. The rats were randomly divided into four groups as the control, DEN treated (50 mg/kg b.w.), DEN+6-gingerol (each 50 mg/kg b.w.), and 6-gingerol only. To evaluate the hepatoprotective effects, liver function enzymes (ALT, AST, and ALP), oxidative stress markers (SOD, GSH, GST, and TAC), lipid peroxidation, inflammatory markers (CRP, TNF- α, IL-6, and ICAM1), haematoxylin and eosin staining, Sirius red staining, immunohistochemistry, and electron microscopy were performed. The results showed a significant increase in liver function enzymes, oxidative stress, and inflammatory markers in the DEN-treated group as compared to the control group. Besides this, altered architecture of hepatocytes (infiltration of inflammatory cells, congestion, blood vessel dilation, and edema), abundant collagen fiber and organelle structures like distorted shaped and swollen mitochondria, and broken endoplasmic reticulum were noticed. The administration of 6-gingerol significantly ameliorated the biochemical and histopathological changes. The increased expression of TNF- α protein was noticed in the DEN-treated group whereas the administration of 6-gingerol significantly decreased the expression of this protein. Based on these findings, it can be suggested that 6-gingerol may be an alternative therapy for the prevention and treatment of liver diseases.